NURSING DIAGNOSTICS IN NEUROSURGERY POST-OPERATIVE. - de Castro Santos, Leonice Nascimento; Gonçalves Aquino, Raísa; Alfradique de Souza, Priscilla; Magalhães da Silva, Natália Chantal; Affonso Luna, Aline (Journal of Nursing UFPE / Revista de Enfermagem UFPE, 2019)
Objective: to verify nursing diagnoses in patients in the postoperative period of neurosurgery. Method: this is a bibliographic, descriptive, integrative literature review study, searching the LILACS, CINAHL databases and the SciELO Virtual Library. The results were presented as figures. Results: a total of 256 articles were found. At the end, three were included, with levels of evidence B2 and B3. Regarding the type of design, two prospective cross-sectional studies and the third retrospective study were characterized. The ten ND found predominantly related to the domains "activity / rest" (domain 4) and "safety / protection" (domain 11), with four NDs in each. Conclusion: we identified, although the publications are still scarce, specifically proposed for the care of patients in the postoperative period of neurosurgery. It is essential, among the actions of nurses in the perioperative period, the identification of diagnoses and the appropriate planning of nursing care to thus meet the needs of each patient holistically.